2022
DOI: 10.3389/fsurg.2022.852097
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Time of Surgery on the Outcome after Surgical Stabilization of Rib Fractures in Severely Injured Patients with Severe Chest Trauma—A Matched-Pairs Analysis of the German Trauma Registry

Abstract: PurposeIn severely injured patients with multiple rib fractures, the beneficial effect of surgical stabilization is still unknown. The existing literature shows divergent results, and the indication and especially the right timing of an operation are the subject of a broad discussion. The aim of this study was to determine the influence of the time point of surgical stabilization of rib fractures (SSRF) on the outcome in a multicenter database with special regard to the duration of ventilation, intensive care,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
3
0
4
Order By: Relevance
“…Our findings have implication for interpreting the literature surrounding timing of SSRF. Specifically, this predominantly retrospective literature has found that earlier SSRF is associated with improved outcomes, the implication of which is a causal relationship between early fixation of unstable fractures leading to improved pain control and pulmonary mechanics ( 14 , 15 , 20 ). However, these analyses are subject to confounding by severity of injury which, in turn, influences the period of resuscitation in a damage control approach, likelihood of additional urgent procedures, and ability to obtain consent for SSRF ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings have implication for interpreting the literature surrounding timing of SSRF. Specifically, this predominantly retrospective literature has found that earlier SSRF is associated with improved outcomes, the implication of which is a causal relationship between early fixation of unstable fractures leading to improved pain control and pulmonary mechanics ( 14 , 15 , 20 ). However, these analyses are subject to confounding by severity of injury which, in turn, influences the period of resuscitation in a damage control approach, likelihood of additional urgent procedures, and ability to obtain consent for SSRF ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study [ 19 ], the primary endpoint showed that the overall duration of hospital stay was 23.44 days in the early surgery group and 28.50 days in the delayed surgery group. The sample size was calculated according to an alpha of 0.05 and a statistical power of 80%, and 384 patients were enrolled (192 in each category).…”
Section: Methodsmentioning
confidence: 99%
“…Becker [ 11 ] reported that most MRF patients presented rib fracture fixation for more than 48 h, while there may be an increased rate of complications with longer intensive care units (ICUs) and hospital times. Recently, a matched-pairs analysis of the German trauma registry showed that early rib fracture fixation can decrease ICU stay and shorten the duration of ventilator use [ 17 ]. Regrettably, almost all of the studies had small sample sizes or were retrospective studies.…”
Section: Introductionmentioning
confidence: 99%
“…Die Indikationen für die operative Stabilisierung der Thoraxwand haben sich in den vergangenen 10 Jahren rasant weiterentwickelt, da neue und durch experimentelle Untersuchungen biomechanisch erprobte Osteosynthesesysteme auf den Markt gekommen sind, aber vor allem auch multiple, umfangreiche prospektiv randomisierte Studien, retrospektive Datenanalysen, Metaanalysen, randomisierte Kontrollstudien und zahlreiche klinische Studien sowie Datenbankauswertungen erfolgt sind [10]. Die Ergebnisse zeigen auf, dass durch eine frühzeitige TxWR der Krankenhausaufenthalt, die Intensivliegedauer und die Beatmungsdauer signifikant gesenkt werden können [4,5,10,12,17,19,21,26,29,31,38,39,49]. Pieracci et al (2018) zeigten erstmals in einer prospektiv randomisierten Multicenterstudie, dass mit jedem Tag einer nicht versorgten TxWI die Wahrscheinlichkeit der Pneumonie um 31 %, die Wahrscheinlichkeit einer Tracheotomie um 26 % und die Rate an Langzeitbeatmung um 27 % ansteigt [39].…”
Section: Indikationen Für Die Operative Thoraxwandrekonstruktionunclassified
“…Aber auch Monoverletzungen des Thorax spielen eine große Rolle und nehmen mit ca. 10 % aller verletzten Patienten einen relevanten Anteil in der täglichen Versorgung ein [4,5]. Dabei ist es jedoch eine unerlässliche Voraussetzung für die korrekte Indikationsstellung der richtigen Versorgungsstrategie einer thorakalen Verletzung, diese vollumfänglich zu erfassen und differenziert mögliche Folgen und das Komplikationspotenzial sowohl der operativen als auch der nicht operativen Strategie abzuschätzen.…”
Section: Introductionunclassified